2011
DOI: 10.1080/10511970903515323
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Mathematics Placement: An Analysis of Advising and Enrollment Data

Abstract: The mathematics placement process at the University of Northern Colorado includes brief faculty-student interviews, during which faculty members suggest mathematics courses for students in their first year at the university. Data from a sample of 1466 students admitted in the fall of 2007 were analyzed to assess the effectiveness of the placement interview. Logistic regression was used to model student success in the first university mathematics course as a function of variables available from university recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…The Fitchett et al (2011) study concluded the process was successful (80%) when the students took the recommended course with two exceptions. When the students took MATH 131 or MATH 127, the success rate was much lower even if those courses were recommended.…”
Section: Institutional Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…The Fitchett et al (2011) study concluded the process was successful (80%) when the students took the recommended course with two exceptions. When the students took MATH 131 or MATH 127, the success rate was much lower even if those courses were recommended.…”
Section: Institutional Contextmentioning
confidence: 99%
“…The School of Mathematical Sciences had a process that included trained instructors or graduate students who met with all first-time freshmen during summer orientation sessions (See Fitchett, King, & Champion, 2011). The purpose of these meetings was to provide advice regarding the proper mathematics course each freshman should take.…”
Section: Institutional Contextmentioning
confidence: 99%
“…The second step in the proposed solution, in conjunction with the creation of the MAT 1125 Integrated Precalculus I course, was a new placement grid that incorporated both ACT/SAT math scores and the high school GPA for placement into the first semester mathematics course. It has been noted in several studies that placement exams or simply using one measure of assessment is not proficient at placing students successfully within mathematics courses [3], [4]. This possibly incorrect placement has the potential of causing a negative impact if not caught early enough in the program, also then serving as a factor in declining retention and/or graduation rates.…”
Section: Placement Matrixmentioning
confidence: 99%
“…This possibly incorrect placement has the potential of causing a negative impact if not caught early enough in the program, also then serving as a factor in declining retention and/or graduation rates. Research on what to use for correct placement has indicated that a combination of level of high school mathematics courses taken, overall high school GPA, ACT/SAT math score, and number of mathematics courses taken during high school shows a stronger correlation between success in the first university mathematics course than only using a mathematics placement exam [4]. In response to needing some form of placement, studies suggest using multiple measures, most widely that of the high school GPA and prior mathematics background in conjunction with assessment scores [5].…”
Section: Placement Matrixmentioning
confidence: 99%
See 1 more Smart Citation